The influence of instruction on isometric mid-thigh pull force-time variables - McCormick, B.; MacMahon, C.; Talpey, S.; James, L. (International Journal of Strength and Conditioning, 2022)
Purpose: The isometric mid-thigh pull (IMTP) is commonly used to assess maximal and rapid (i.e., explosive) strength in athlete populations. The conventional IMTP instruction is to pull "as hard and fast as possible" (CON). However, previous studies using other isometric tests indicate that the use of `hard` and `fast` independently can result in different test outcomes. This investigation assessed the impact of a `hard` only (HARD) and `fast` only (FAST) instruction on IMTP kinetics when compared to the conventional combined instruction. Methods: Over three separate testing sessions, 17 National level, male, youth footballers (age: 16.4±1.3yr, mass: 69.7±8.0kg, height: 1.75±0.07m) completed three trials of the IMTP under each instruction. Peak force (N) and rapid force production, measured as impulse (N.s-1) over 50ms, 75ms, 100ms, 150ms, and 200ms were extracted and brought forward for analysis. To determine the presence of a statistical difference between conditions, a repeated measures ANOVA was employed while Cohen`s d effects sizes were used to quantify the magnitude of practical difference between each condition. Results: There was no significant or practically relevant impact of instruction condition on peak force (P > 0.05, d=0.08-0.27), or impulse over any time frame (P > 0.05, d=0.01-0.16). Conclusion: Practitioners can be confident that the conventional IMTP instruction is suitable for continued use in this athlete population.